A atividade de relações públicas e sua contribuição para a criação de significado no CEFET/RJ: uma abordagem de interação entre os públicos organizacionais - Bottino, Marilda Barroso (2013)
This research investigates how meaning is created daily in the Federal Center of Technological Education environment - CEFET / RJ and how it can be influenced by explicit politics in your area of public relations. The analysis is based on the flows of information and knowledge produced by internal stakeholders (teachers and administratives) of the institution. For that fetches theoretical contributions fundamentally Weick (1995 ), which introduces the concept of organizational sensemaking in public relations with its environment, and Nonaka and Takeuchi (2008 ) propose that conversion mechanisms capable of generating and sharing new knowledge. An exploratory study involving 16 teachers and 27 administrative, where we seek to come to the fore questions regarding not only the public but also to the institution of the public among themselves, particularly the relationship between faculty and administration is done. The results point to the different perspectives of different professional segments and how political communication and strategic management of the institution have more reinforced than mitigated these difficulties. Therefore it is proposed to end a set of tools that can support a future revision of the politic, highlighting the role to be played in this context by public relations professionals